Excilamps and their Applications. Issue 1 (1st December 2015) - Lomaev, Mikhail I.; Sosnin, Eduard A.; Tarasenko, Victor F.
Abstract: An innovative class of sources of spontaneous ultraviolet and vacuum ultraviolet radiation, the so‐called excilamps, based on the nonequilibrum radiation of exciplex or excimer molecules, is described. The design and some technical characteristics of traditional excilamps excited by a dielectric barrier discharge are presented. The data concerning newly developed types of excilamps excited by runaway‐electrons‐preionized diffuse discharge both in single and pulse‐periodic modes are given as well. Some novel applications of excilamps in photochemistry, the effect of ultraviolet and vacuum ultraviolet radiation on the physiological action of living organisms, photosynthesis, and growth of plants, and the use of excilamps for pre‐sowing treatment of seeds are explained in detail. Abstract : Excilamps are effective sources of spontaneous narrowband radiation in the ultraviolet or vacuum ultraviolet spectral regions. They operate due to formation and subsequent decay of excimer or exciplex molecules. Long lifetimes and the possibility to change the radiation wavelength with the choice of working excimer/exciplex molecules are attractive features of photoreactors based on excilamps.